Assessing available information on the burden of sepsis: global estimates of incidence, prevalence and mortality - Jawad, Issrah (Edinburgh University Global Health Society, 2012)
OBJECTIVE: Sepsis is a complex and hard-to-define condition with many different interactions with other disorders. Presently, there are no estimates of the burden of sepsis and septicaemia at the global level and it was not included in the initial Global Burden of Disease study. Non-maternal sepsis has only recently received attention as a substantial global public health problem. The aim of this study was to assess available data on the burden of non-maternal sepsis, severe sepsis and septic shock in the community and to identify key gaps in information needed to estimate the global burden of sepsis. METHODS: Literature review of English language-based studies reporting on the incidence, prevalence, mortality or case-fatality of sepsis, severe sepsis and septic shock. The available literature was searched using the MEDLINE database of citations and abstracts of biomedical research articles published between 1980 and 2008. FINDINGS: 8 studies reported incidence of sepsis, severe sepsis or septic shock at the national level (4 from the USA and 1 from Brazil, the UK, Norway and Australia). No studies on the incidence, prevalence, mortality or case-fatality from sepsis in developing countries were found. The population sepsis incidence ranged from 22 to 240/100 000 (most plausible estimates ranged from 149 to 240/100 000); of severe sepsis from 13 to 300/100 000 (most of the estimates were between 56 and 91/100 000); and of septic shock 11/100 000. Case-fatality rate depends on the setting and severity of disease. It can reach up to 30% for sepsis, 50% for severe sepsis and 80% for septic shock. While the data were compiled using strict inclusion and exclusion criteria, a degree of uncertainty still exists regarding the reported estimates. CONCLUSION: The few national-level reports available allow only a very crude estimation of the incidence of sepsis in developed countries while there is apparent lack of data from developing countries. A clear and universal definition of sepsis as well as the development of a sound epidemiological framework to begin addressing the magnitude of this problem is urgently needed through research in developing countries.